Performance Measurement of State University with Service Public Financial Management Board in Indonesia - Asri Diah Susanti; Anni Aryani (Jurnal Akuntansi dan Bisnis, 2014)
This study aims to determine the pattern of university performance management Public Service Board (BLU). To measure the size of the financial performance of the university using the ratio Composite Financial Index (CFI) Higher Education made ​​by KPMG in the financial statements of public universities in Indonesia. This ratio includes the primary reserve ratio, net income ratio, return on net assets ratio, and the viability ratio. To determine the performance of three ways, namely by comparing the performance of units before and after use patterns BLU financial management, comparing the performance of units BLU and units non-BLU, examine the effect of flexibility on performance. The analytical tool used in this research is to use your paired sample t-test, independent sample t-test, and linear regression. The results showed that there were different university performance before and after using the BLU management scheme, there are different patterns of performance management BLU and universities with the pattern of non-BLU, and flexibility affect the performance. This difference is seen in the primary reserve ratio and the net income ratio. Return on net assets ratio showed no significant results, whereas the viability ratio can not be measured because only two universities that reported this ratio. The university is the University of Indonesia and Hasanuddin University.